Transmissão de áudio com baixa latência sobre redes wireless IEEE 802.11 com foco em acessibilidade para o cinema digital - Guedes, Caio Marcelo Campoy (2021)
The transmission of audio reinforcement from a server to mobile phones used by the hearing impaired during the presentation of a film in cinemas is an example among applications that use Wi-Fi networks and require the transmission of audio with low latency, synchronism and resilience. In this application, it is meant that the delay between capturing and repro- ducing the audio stream lays below 40 ms, a requirement that focus on the optimization of encoding, transmission and decoding of the solution. This study aims to develop a client-server solution capable of transmitting audio in real time over IEEE 802.11 wireless networks between a server and clients running on mobile devices. The work seeks to limit the maximum latency between source and player to a threshold of 40 milliseconds defined as a threshold for the perception of lip sync. Maintaining low latency by avoiding variations in delay and packet loss in volatile environments such as wireless networks is a complex problem. Therefore, aiming for maximum resilience, the solution makes use of Forward Error Correction and proposes the use of temporal redundancy to mitigate the undesirable effects caused by the loss and discarding of delayed packages. Additionally, a new adaptive algorithm is proposed and used to adjust the buffer of playback in order to mitigate the network jitter.